2021
DOI: 10.5091/plecevo.2021.1839
|View full text |Cite
|
Sign up to set email alerts
|

Moss phyllid morphology varies systematically with substrate slope

Abstract: Background and aims – Tracheophyte leaf morphology is well studied but it is unclear if the findings generalize to poikilohydric plants. We tested combinations of hypotheses to determine if microhabitat characteristics, including light exposure, moisture availability, and substrate slope, controlled for morphological differences between upright and prostrate growth forms, affect phyllid surface area and costa length of mosses.Material and methods – We quantified mean phyllid surface-area and costa lengths for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The slope gradient was negatively correlated with CL, CW, LL, and L/W (Figure 3). This result was consistent with previous studies, such as that by Turberville et al, which reported a smaller phyllid surface area in mosses growing on vertical substrates [27]. In general, there is a negative relationship between canopy and slope in montane regions, due to the high slope effect of strong intense light, scare water resource and frequent disturbance [28].…”
Section: Morphological Adaptations To the Microhabitat Gradientsupporting
confidence: 92%
“…The slope gradient was negatively correlated with CL, CW, LL, and L/W (Figure 3). This result was consistent with previous studies, such as that by Turberville et al, which reported a smaller phyllid surface area in mosses growing on vertical substrates [27]. In general, there is a negative relationship between canopy and slope in montane regions, due to the high slope effect of strong intense light, scare water resource and frequent disturbance [28].…”
Section: Morphological Adaptations To the Microhabitat Gradientsupporting
confidence: 92%
“…Previous sampling experience 31,45 showed that Viridiscus species are often found in mosses and lichens growing on rapidly draining vertical surfaces (see e.g. 46 ) such as the sides of rocks (Fig. 15), gravestones, and tree trunks in human-altered environment.…”
Section: Sample Collection and Processingmentioning
confidence: 99%